Successful management of diffuse unilateral subacute neuroretinitis with anthelmintics, and intravitreal triamcinolone followed by laser photocoagulation - Behzad Safarpour Lima; Alireza Ramezani; Masoud Soheilian; Ali Rastegarpour; Danial Roshandel; Shima Sayanjali (Journal of Ophthalmic & Vision Research, 2016)
Purpose: Diffuse unilateral subacute neuroretinitis (DUSN), a form of posterior uveitis, is secondary to the presence of a highly motile nematode in the intraretinal or subretinal space. Herein, we report a case of DUSN that was successfully managed by an intravitreal injection of triamcinolone and laser therapy. Case Report: A middle-aged man with complaint of decreased vision and marked unilateral vitritis and neuroretinitis. Fluorescein angiography revealed disc leakage, vessel wall staining, and diffuse track-like transmission defects of the RPE. Optical coherence tomography confirmed the subretinal location of the worm. The patient received oral thiabendazole and an intravitreal injection of triamcinolone acetonide. After 10 days, media haziness decreased, and a live motile subretinal worm was identified. Direct laser photocoagulation was performed to destroy the worm. After two months, a localized chorioretinal scar developed and no further active inflammation and subretinal worms were detected. Conclusion: Intravitreal steroids can be used safely in cases with DUSN and may help detect the causative worm for applying laser photocoagulation.